CESAREAN SCAR ECTOPIC PREGNANCY IN RELATION TO PREVIOUS OBSTETRICAL HISTORY - Arif, Gash Khalid; Fattah, Chro Najmaddin (Journal of Sulaimani Medical College, 2023)
Background Cesarean scar ectopic pregnancy (CSEP) is the implantation of a gestational sac inside the scar of a previous cesarean section (C/S). CSEP is a life-threatening condition that needs early management. Objectives The study aimed to know the associations between CSEP and previous obstetrical history. Patients and Methods Twenty-seven women with CSEP who were admitted to the Sulaimani Maternity Teaching Hospital from September 2019 to October 2021 were collected for this cross-sectional study. Complete obstetrical history, clinical features, the interval between the last C/S and CSEP, mode of diagnosis, and types of management were recorded. Results The mean of maternal age, gravidity and parity were 32.14±4.63 years (range, 24 to 40 years), 3.73±1.75 (range, 1 to 8) and 2.36±1.33 (range, 1 to 6), respectively. The majority (74.1%) had no significant medical diseases. The mean interval between the last C/S and CSEP was 2.6±1.8 years, and 92.6% complained of vaginal bleeding. The association of gravidity with CSEP presentation was statistically significant. Only 22.2% had a history of one prior C/S alone; however, 74.1, 14.8%, and 3.7% of patients had two, three, and four previous C/Ss, respectively. Besides, the associations of first and second C/Ss with obstetricians’ experience who performed the C/Ss were statistically significant. Conclusion The risk of CSEP increases when the frequency of gravidity and previous C/S increases.
Keywords: Cesarean section; Ectopic pregnancy; Scar ectopic